Tip gap size effects on thermal performance of cavity-winglet tips in transonic turbine cascade with endwall motion. (27th June 2017) - Zhong, Fangpan; Zhou, Chao
Abstract: The thermal performance of two cavity-winglet tips with endwall motion is investigated in a transonic high pressure turbine cascade, which operates at an engine representative exit Mach number of 1.2 and an exit Reynolds number of 1.7 × 10 6 . The numerical method is first validated with experimental data and then used to investigate blade heat transfer at three different tip clearances of 1.1, 2.1 and 3.1% chord. The effects of relative endwall motion are considered. The present results show that as the size of the tip gap increases, the heat transfer coefficient and heat load on the tip increases. The winglet geometries on the blade tip mainly affect the tip flow structure close to them. At a larger tip clearance, the size of the separation bubble above the pressure side winglet increases. The heat transfer coefficient is high on the pressure side winglet due to the flow reattachment at all tip clearances. Within the tip gap, when the size of the tip clearance increases, the size of the cavity vortex increases and the cavity scraping vortex due to relative endwall motion becomes smaller. The impingement of the both two vortexes can lead to high heat transfer coefficient on the cavity floor surface. On the blade suction surface, when the size of the tip clearance increases, the heat transfer coefficient of the cavity tip increases, but those of the winglet tips decreases. The heat transfer coefficient is high on the side surface of the suction side winglet at all tip clearances because of the tip leakage flow impingement.